Credit Nation : Property Laws and Institutions in Early America - Priest, Claire (Book collections on Project MUSE., 2021)
How American colonists laid the foundations of American capitalism with an economy built on credit. Even before the United States became a country, laws prioritizing access to credit set colonial America apart from the rest of the world. Credit Nation examines how the drive to expand credit shaped property laws and legal institutions in the colonial and founding eras of the republic.